Experimental investigations on the chlorine-induced corrosion of HVOF thermal sprayed Stellite-6 and NiAl coatings with fluidised bed biomass/anthracite combustion systems. (15th March 2021) - Chi, Hetian; Pans, Miguel A.; Bai, Mingwen; Sun, Chenggong; Hussain, Tanvir; Sun, Wei; Yao, Yuge; Lyu, Junfu; Liu, Hao
Highlights: HVOF thermal sprayed coatings tested in BFB and CFB combustion systems. Corrosion development for all specimens depends on the fuel ash properties. Stellite-6 showed excellent anti-corrosion ability in both combustion systems. NiAl spalled off due to the formation of Al2 O3 at the coating/substrate interface. Anthracite coal ash-derived Al-rich scales hindered the corrosion development. Abstract: Stellite-6 (Co-based) and NiAl coatings (Ni-based) were deposited via HVOF spraying onto 304 stainless steels and tested in a 20 kWth biomass fired bubbling fluidised bed (BFB) combustor for 20 h and an industrial scale anthracite fired CFB boiler for 1630 h. Stellite-6 showed excellent corrosion resistance in both fluidised bed combustion systems because of the formation of the outermost Cr2 O3 layer and the spinel CoCr2 O4 beneath, whereas NiAl coatings' anti-corrosion performance was significantly depleted due to the chlorine attack, and the resultant formation of Al2 O3 layer at the coating/substrate interface finally led to coating spallation in both systems.